The role of teachers' instrumental and emotional support in students' academic buoyancy, engagement, and academic skills: A study of high school and elementary school students in different national contexts. (August 2022) - Granziera, Helena; Liem, Gregory Arief D.; Chong, Wan Har; Martin, Andrew J.; Collie, Rebecca J.; Bishop, Michelle; Tynan, Lauren
Abstract: In this investigation of high school students ( N = 2510) in Singapore (Study 1) and elementary school students ( N = 119) in Australia (Study 2), we examined the role of instrumental and emotional forms of teacher support in students' academic buoyancy and academic outcomes (engagement and academic skills). In both studies, perceived instrumental support (but not perceived emotional support) was positively associated with academic buoyancy (moderate effect size in Study 1, large effect in Study 2). In Study 1, academic buoyancy was positively associated with students' academic engagement (specifically, effort and persistence [large effect], perceived importance of school [moderate effect], and feelings of school belonging [moderate effect]). In Study 2 academic buoyancy was positively associated with gains in students' academic skills and engagement (specifically, class participation [large effect] and future aspirations [large effect]). In both studies, there was tentative support for a mediating role of academic buoyancy linking students' perceived teacher support to academic outcomes. Highlights: We examined academic buoyancy in high (Singapore) and elementary school (Australia). Perceived support from teachers positively predicted students' academic buoyancy. Academic buoyancy predicted students' academic engagement. Academic buoyancy predicted academic skill gains. Tentative evidence for buoyancy linking teacher support to academic outcomes.